A Novel Mutation in Helical Domain 2 of NOD2 in Sporadic Blau Syndrome. (17th February 2018) - Jain, Lubhani; Gupta, Namrata; Reddy, Mamatha M.; Mittal, Ruchi; Barik, Manas Ranjan; Panigrahi, Bharat; Monie, Tom; Basu, Soumyava
ABSTRACT: We report a 12-year-old girl who presented with bilateral granulomatous anterior uveitis accompanied by boggy arthritis of knee and ankle joints, intermittent fever, and nodular skin rash. She was diagnosed with sporadic Blau syndrome (early-onset sarcoidosis) based on above clinical signs and presence of non-necrotising granuloma on iris biopsy. DNA sequencing revealed a previously unreported heterozygous mutation consisting of a G>A transition in exon 4 of the NOD2 gene. This resulted in a glutamic acid to lysine substitution in helical domain 2 of the nucleotide binding and oligomerization (NACHT) region, possibly reducing efficiency of auto-inhibition in NOD2 signaling. Interestingly, the ocular inflammation resolved completely following therapeutic vitrectomy in both eyes whereas the systemic symptoms of fever and arthritis continued to wax and wane while on treatment with oral methotrexate and corticosteroids.